Análisis de la Flexo Tracción del Concreto Permeable - Solano-Cerdas, Cindy (Instituto Tecnológico de Costa Rica, 2009)
The principal goal in this project is to determine the ruptura modulus or the strength to the slip tensile of the porous concrete and by the way correlate this datas with the strength to the compression that this knd of material has. Besides it pretens to made the design of porous concrete pavement and give an exact account of advantages that this material has according the pluvial recolection and the enviromental protection. To determinate the ruptura modulus of te porous concrete there was applicated a process of test in the days 7th, 14th and 28th, specimens through the slip test. Also, tol et know its strength to the tensile, there was used the indirect tensile test or brazilian test taking, in the last case, specimens and to fail at the same ages mencionated before. According to the last investigations that determinated the strength of the compression, it makes the correlate between the given results and the strength values, and gives result the relation between the ruptura modulus and the strength to the compression at the porous concrete. Likewise, there was proceed the design of porous concrete pavement for a project that is localized in Cachi, Paraiso, Cartago. This design was made with the procedure of the AASHTO and there was taked like reference to determine the concrete ruptura modulus the final result of this investigation. Finally, there were compare this kind of pavements with other kinds in the economical aspect.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2009.
Keywords: Resistencia; Compresión; Modo de falla; Agregados; Compactación; Aditivos